2015
DOI: 10.1007/s10653-015-9784-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Field evaluation of intensive compost application on Cd fractionation and phytoavailability in a mining-contaminated soil

Abstract: A field experiment was conducted to investigate the effect of chicken manure compost on the fractionation of cadmium (Cd), soil biological properties and Cd uptake by wheat in a soil affected by mining activities in Hubei province, China. Compost was applied at five levels (0, 27, 54, 108, 216 t ha(-1)), and winter wheat (Triticum aestivum L.) was chosen as an indicator plant. Results showed that the application of compost increased soil pH and the content of total phosphorus and organic matter. Soil biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…The positive effects of organic waste and fermented sugar beet on soil biodiversity as well as the activities of dehydrogenase and acid phosphatase were observed by Bending et al [55] and Kohler et al [56]. The studies conducted by Mingorance et al [57] and Li et al [42] also revealed the positive influence of compost and Lycopersicon esculentum (Mill. ), Lolium perenne L., Pachyrhizus ahipa (Wedd.)…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The positive effects of organic waste and fermented sugar beet on soil biodiversity as well as the activities of dehydrogenase and acid phosphatase were observed by Bending et al [55] and Kohler et al [56]. The studies conducted by Mingorance et al [57] and Li et al [42] also revealed the positive influence of compost and Lycopersicon esculentum (Mill. ), Lolium perenne L., Pachyrhizus ahipa (Wedd.)…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, the high efficiency of Zn, Cd and Pb immobilization by fly ash and red mud during an aided phytostabilization was established by Lopareva-Pohu et al [41] and Pavel et al [9]. The other materials that have proved to be efficient stabilizers of Pb, Cd and Zn in the soil from mining areas are green compost and compost with a high content of humic acids [15,42,43]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composting increases soil OM, microbial activity, plant growth, and vegetable production [82]. Moreover, 69.6% to 75% and 10.3% to 18.4% of Cd in stems and seeds of wheat, respectively, are reduced by adding 27-54 t ha −1 of compost [84]. Khedr et al [85] reported that adding vermicompost can reduce extractable/available Cd by up to 98% in soil under wheat cultivation.…”
Section: Using Organic Amendmentmentioning
confidence: 99%
“…Phytostabilization may be supported using a variety of additives, including composts and mineral sorbents [29]. Previous studies [30][31][32][33] have shown that individual materials used as additives aid phytostabilization. In this article, the authors recognized the impact of new amendments in the form of mineral and organic mixture on the process of aided phytostabilization in a soil artificially contaminated with Ni, enabling their use under in-situ conditions.…”
Section: Introductionmentioning
confidence: 99%